2020
DOI: 10.4236/msa.2020.119043
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization on Physico-Mechanical and Structural Properties of Sawdust Reinforced Acrylonitrile Butadiene Styrene (ABS) Composites

Abstract: The sawdust reinforced Acrylonitrile Butadiene Styrene (ABS) composites were prepared by using hot press molding machine for five different wt% (0%, 5%, 10%, 15% and 20%) at 180˚C temperature and 50 KN load. Sawdust was collected from local saw mill of Savar, Dhaka, Bangladesh and ABS polymer was collected from local market of Dhaka, Bangladesh. In this study, different properties of composites like physical (bulk density and water absorption), mechanical (tensile properties and hardness) and structural (Fouri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Mechanical properties of NFPCs with ABS as the polymer matrix have been extensively investigated by various research groups across the world. Neher et al [2,37] examined the mechanical and physical properties of ABS/palm fiber composites and concluded that the tensile strength and flexural strength of the composite material decrease with the introduction of fiber content, but that the stiffness of the material increases. Similarly, Martins et al [38] observed that the introduction of fiber content considerably increases the stiffness of ABS/textile fiber composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical properties of NFPCs with ABS as the polymer matrix have been extensively investigated by various research groups across the world. Neher et al [2,37] examined the mechanical and physical properties of ABS/palm fiber composites and concluded that the tensile strength and flexural strength of the composite material decrease with the introduction of fiber content, but that the stiffness of the material increases. Similarly, Martins et al [38] observed that the introduction of fiber content considerably increases the stiffness of ABS/textile fiber composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…The hardness of the composite is measured using an H-1000 portable hardness testing machine, as shown in Figure 5, according to ASTM A956-06 [9][10][11]. One of the four most commonly used techniques for metal hardness measurement is the Leeb Rebound Hardness Test [9,10,12], patented by the Swiss company Proceq SA. The conventional approaches are based on well-defined measurements of physical indentation hardness.…”
Section: Hardness Testmentioning
confidence: 99%
“…The elastic modulus of the composite varies with the increase in rice husk content, gradually increasing at first but showing a sudden decrease if the rice husk content reaches 10% [9]. Also, the water absorption of sawdust Acrylonitrile Butadiene Styrene (ABS) composite increases with the increase of soaking time and fibre content [10]. Hardness tests performed using the standard Leebs Hardness test showed a decrease in hardness with the increase in fibre content, a similar trend is noted for tensile strength [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alumina nanocomposites and carbon nanotubes with ABS improve hardness, Young'smodulus, tensile strength, and flexural modulus [5]- [6]. The rheological, thermal, and mechanical properties were studied, and it reported that 20wt% of Gr in ABS decreases melt flow index (MFI) and ABS+20wt% of Gr composites exhibited the highest heat capacity (0.84 J/g) [7]- [8].…”
Section: Introductionmentioning
confidence: 99%